2006
DOI: 10.1210/en.2006-0081
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor Receptor-2 Expression Is Induced by 17β-Estradiol in ZR-75 Breast Cancer Cells by Estrogen Receptor α/Sp Proteins

Abstract: Vascular endothelial growth factor receptor-2 kinase insert domain receptor (VEGFR2/KDR) is critical for angiogenesis, and VEGFR2 mRNA and protein are expressed in ZR-75 breast cancer cells and induced by 17beta-estradiol (E2). Deletion analysis of the VEGFR2 promoter indicates that the proximal GC-rich region is required for both basal and hormone-induced transactivation, and mutation of one or both of the GC-rich motifs at -58 and -44 results in loss of transactivation. Electrophoretic mobility shift and chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
62
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(71 citation statements)
references
References 52 publications
9
62
0
Order By: Relevance
“…6). Moreover, we have recently reported similar ERa and Sp interactions with the VEGFR2 promoter in ZR-75 cells using a ChIP assay (Higgins et al 2006b). Our results demonstrate for the first time that hormonal activation of genes containing E 2 -responsive GC-rich promoters in MCF-7 cells requires ERa interactions with Sp1, Sp3, and Sp4.…”
Section: Colocalization Of Era With Sp1 and Sp4mentioning
confidence: 65%
See 3 more Smart Citations
“…6). Moreover, we have recently reported similar ERa and Sp interactions with the VEGFR2 promoter in ZR-75 cells using a ChIP assay (Higgins et al 2006b). Our results demonstrate for the first time that hormonal activation of genes containing E 2 -responsive GC-rich promoters in MCF-7 cells requires ERa interactions with Sp1, Sp3, and Sp4.…”
Section: Colocalization Of Era With Sp1 and Sp4mentioning
confidence: 65%
“…for hormone-induced transactivation in breast cancer and other cell lines (Porter et al 1996, Duan et al 1998, Sun et al 1998, 2005, Qin et al 1999, Xie et al 1999, 2000, Byrne et al 2000, Salvatori et al 2000, Saville et al 2000, Stoner et al 2000, Tanaka et al 2000, Castro-Rivera et al 2001, Li et al 2001, Bruning et al 2003, Jacobson et al 2003, Khan et al 2003, Ngwenya & Safe 2003, Schultz et al 2003, 2005, Fujita et al 2004, Bardin et al 2005, Zhao et al 2005, Higgins et al 2006b. In this study, we have also used RNA interference and small inhibitory RNAs (siRNAs) for Sp1 (iSp1), Sp3 (iSp3), and Sp4 (iSp4) to investigate the role of individual Sp proteins in ERa/Sp-mediated transactivation in MCF-7 cells.…”
Section: Role Of Sp Proteins Of Hormonal Activation Of Psp1mentioning
confidence: 99%
See 2 more Smart Citations
“…We chose the TFF1 promoter because it is associated with Sp1 or Sp3, which recruits the Sin3 HDAC complex (28). In X-ChIP experiments, we and others have demonstrated that the TFF1 promoter is associated with Sp1 or Sp3 as well as HDAC2 and 1 in the presence or absence of estradiol (22,29). Because our cross-linking study showed that the phosphorylated forms of HDAC2 were preferentially cross-linked to DNA, we assumed that it was the phosphorylated forms of HDAC2 that were detected at the TFF1 promoter.…”
Section: Phosphorylated Hdac2 Forms Are Associated With Promotermentioning
confidence: 99%